(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The museum is an institution with fundamental functions, including the collection, preservation, and maintenance of material documents, whether they are historical documents or related to arts and sciences. One of its primary tasks is to preserve the national and human heritage and transmit it to future generations. Based on this, museums have evolved from their old form as treasure troves and storage and protection facilities to encompass broader and more comprehensive functions. Museums now serve as cultural centers to benefit the local community’s activities and educate young individuals to build their character in alignment with national and human concepts.